Enhancing Electrotransfection Efficiency through Improvement in Nuclear Entry of Plasmid DNA - Lisa D. Cervia; Chun-Chi Chang; Liangli Wang; Mao Mao; Fan Yuan (Elsevier, 2018)
The nuclear envelope is a physiological barrier to electrogene transfer. To understand different mechanisms of the nuclear entry for electrotransfected plasmid DNA (pDNA), the current study investigated how manipulation of the mechanisms could affect electrotransfection efficiency (eTE), transgene expression level (EL), and cell viability. In the investigation, cells were first synchronized at G2-M phase prior to electrotransfection so that the nuclear envelope breakdown (NEBD) occurred before pDNA entered the cells. The NEBD significantly increased the eTE and the EL while the cell viability was not compromised. In the second experiment, the cells were treated with a nuclear pore dilating agent (i.e., trans-1,2-cyclohexanediol). The treatment could increase the EL, but had only minor effects on eTE. Furthermore, the treatment was more cytotoxic, compared with the cell synchronization. In the third experiment, a nuclear targeting sequence (i.e., SV40) was incorporated into the pDNA prior to electrotransfection. The incorporation was more effective than the cell synchronization for enhancing the EL, but not the eTE, and the effectiveness was cell type dependent. Taken together, the data described above suggested that synchronization of the NEBD could be a practical approach to improving electrogene transfer in all dividing cells.